Association between depression and sleep apnoea: a Mendelian randomisation study. Issue 1 (7th February 2021) - Chen, Gui; Xie, Junyang; Liu, Weixing; Liang, Tianhao; Liao, Xiao; Liao, Wenjing; Song, Lijuan; Zhang, Xiaowen
Background: Studies have reported a close relationship between depression and sleep apnoea, yet it is unknown whether these are causally related. Thus, we aimed to determine whether depression is associated with the aetiology of sleep apnoea. Methods: We used publicly available genetic summary data from two large consortia: the Psychiatric Genomics Consortium, with data from 36 single-nucleotide polymorphisms (SNPs) closely associated with major depressive disorder (MDD), and the UK Biobank, including 456 736 patients with sleep apnoea and 766 964 controls. For Mendelian randomisation (MR) analysis, we used the inverse-variance weighted method, weighted median method, MR-Egger regression, MR pleiotropy residual sum and outlier test to retrieve summary data. Analyses were performed using the "TwoSampleMR" package in R. Results: Out of the 36 SNPs associated with MDD, we found statistically significant evidence of a potential causal effect of MDD on the risk of sleep apnoea (OR 1.004, 95% CI 1.001–1.006; p=0.001). Similar results were obtained using the MR-Egger and weighted median methods. Additionally, we found no heterogeneity or pleiotropy. Conclusions: Our findings suggest that depression slightly increases the risk of sleep apnoea. Further investigation of the potential biological mechanisms is necessary. The results of this study show that depression has a potential causal relationship with a higher risk of sleep apnoea, providing evidence for the role of depression in sleep apnoea https://bit.ly/3CJavif